Recent developments in small bowel endoscopy: the "black box" is now open! - Luigina Vanessa Alemanni; Stefano Fabbri; Emanuele Rondonotti; Alessandro Mussetto (Korean Society of Gastrointestinal Endoscopy, 2022)
Over the last few years, capsule endoscopy has been established as a fundamental device in the practicing gastroenterologist's toolbox. Its utilization in diagnostic algorithms for suspected small bowel bleeding, Crohn's disease, and small bowel tumors has been approved by several guidelines. The advent of double-balloon enteroscopy has significantly increased the therapeutic possibilities and release of multiple devices (single-balloon enteroscopy and spiral enteroscopy) aimed at improving the performance of small bowel enteroscopy. Recently, some important innovations have appeared in the small bowel endoscopy scene, providing further improvement to its evolution. Artificial intelligence in capsule endoscopy should increase diagnostic accuracy and reading efficiency, and the introduction of motorized spiral enteroscopy into clinical practice could also improve the therapeutic yield. This review focuses on the most recent studies on artificial-intelligence-assisted capsule endoscopy and motorized spiral enteroscopy.